Doping dependency of chitosan and PAA controlled CdSe quantum dots for catalytic and bactericidal behavior by inhibiting DNA gyrase and DHFR through molecular docking - Hassan, Mudassir; Ikram, Muhammad; Haider, Ali; Shahzadi, Iram; Moeen, Sawaira; Ul-Hamid, Anwar; Ali, Ghafar; Ullah, Hameed [UNESP]; Ebaid, Manal S.; Graeff, Carlos F.O. [UNESP] (Elsevier, 2025)
The presence of toxic dyes in industrial waste dramatically diminishes the beneficial effects of remediation efforts. To overcome the hazardous impacts of dyes on biodiversity and environment, we integrated polymers into nanoparticles to substantially enhance their functionality and performance. 2 and 4 wt% of chitosan (CS) and 3 wt% of polyacrylic acid (PAA) doped cadmium selenide (CdSe) nanostructures (NSs) were prepared by co-precipitation approach. CdSe quantum dots (QDs) exhibit a narrow band gap energy, high solubility, and tunable properties, which are appropriate for redox reactions but show less adsorption and catalytic behavior. In this work, catalytic and antibacterial activities of CdSe QDs enhanced upon the integration of PAA due to increment in surface area confirmed by BET analysis. Furthermore, the addition of CS escalates the dye degradation and microbes evolve to the interaction of CdSe surface with the functional groups of CS. Highly doped CdSe shows significant inhibitory zones (8.65 to 9.30 mm) against gram-positive bacteria Staphylococcus aureus (S. aureus). In addition, the inhibitory activity of CS/PAA-CdSe nanostructures against DNA gyrase and dihydrofolate reductase (DHFR) in S. aureus was elucidated using molecular docking investigations, providing a rationale for their bactericidal action.
Keywords: CdSe; Chitosan; RhB degradation